Exploring in-hospital mobility practices for geriatric patients: insights from a mixed-method study - Lea Kromann Johansen; Trine Schifter Larsen; Jeanette Wassar Kirk; Britt Staevnsbo Pedersen; Barbara Rubek Nielsen; Thomas Kallemose; Thomas Bandholm; Mette Merete Pedersen (BMC Geriatrics)
Abstract Background It is well-established that mobility is very limited among older hospitalized patients and associated with several negative outcomes. Therefore, this mixed-methods study aimed to quantify 24-hour mobility levels in acutely admitted older adults and simultaneously explore clinical practice with regards to mobilization and mobility through an ethnographic field study. Methods Over a 6-week period, hospital mobility was assessed in 44 geriatric patients by SENS motion® activity sensors that the patients wore continuously for 24 h a day during their hospitalization. An ethnographic field study was conducted alongside the cohort study. It included participant observation on the ward and situated conversations with staff, patients, and relatives 2–3 times a week for 4–5 h at different times of the day. The observations were noted in field notes. Activity data were aggregated into a per day measure based on the mean of all available days for a given patient. Also, the per day measures were stratified by walking dependency (walking with or without a walking aid). The field notes were analyzed through a thematic analysis. Results During hospitalization, the patients spent most of their time (22.8 h/per day) in sedentary behavior and only 1.2 h/per day in uptime (walking and standing), including 43 min walking, and took less than 1200 steps daily. The field study revealed that most staff consider mobilization and mobility important tasks. However, mobilizing patients to a chair and performing functional level assessments are prioritized over patient mobility. Also, the patients’ perceived mobility opportunities are limited by the physical environment (e.g., congested hallways) and lack of purposeful activities to engage in. Conclusions This study found low levels of mobility in geriatric inpatients during hospitalization. While mobility is considered important, mobilization to a chair and functional assessments are prioritized over patient mobility, which becomes dependent on the patient’s own initiative. Therefore, environmental adjustment, enhanced interprofessional collaboration, and targeted strategies for integrating mobility into daily care practices are warranted to enhance in-hospital mobility. ClincalTrials.Gov identifier NCT06421246.